Kemampuan Menulis Teks Deskripsi Siswa Kelas VII-G SMP Negeri 1 Kencong - Putri, Maya Iskina; Muti'ah, Arju; Pornomo, Bambang Edi (Lingua Skolastika, 2024)
This study intented to describe the student’s ability in writing descriptive text in the aspects of describing the objects, constructing the structure of the text, and also the language used by the students from VII-G of SMP Negeri 1 Kencong. The study is identified as a Descriptive Quantitative. Meanwhile, the source of the data was chosen through a Purposive Sampling Technique. Furthermore, tests and documentation were used to collect the data. The result of the data analysis revealed that the student’s ability in writing descriptive text in the aspect of describing the object is categorized as good with an overall average of 87.71. Besides, it was also found that the students' ability in writing descriptive text in the aspect of constructing the structure of the text is also classified as good, and it could be noticed from the average score for this aspect which received about 84.11 points. In addition, referring to the finding in the student's ability in writing descriptive text in the aspect of language use, it was found that the student's ability in this aspect is indicated as good with an average of 80.8. Overall, the ability to write descriptive texts for class VII-G students of SMP Negeri 1 Kencong is in the "good" category with an average score of 84.2%.